The Mediating Role of Positive Emotion in the Nexus of Marketing Strategies and Sustainable Marine Tourism: Study on Coral Reef Conservation Area at Mengiat Beach, Bali - Tjokorda Gde Agung Wijaya Kesuma Suryawan; I Wayan Meryawan; Komang Sumerta; I Dewa Agung Ayu Eka Idayanti (Jurnal Indonesia Sosial Teknologi, 2024)
This study investigates the impact of relationship marketing and education-based marketing on sustainable marine tourism, utilizing positive emotion as a mediating factor. Through a quantitative approach and purposive random sampling with 100 respondents, the research underscores the significance of relationship marketing and education-based marketing in shaping positive emotion and its correlation with sustainable marine tourism. Data were collected through questionnaires and analyzed using the Partial Least Square (PLS) method in Smart PLS Version 3.0. Relationship and education-based marketing emerge as critical influencers of positive emotion and contribute positively to sustainable marine tourism. Positive emotion is a crucial mediator, linking emotional experiences to advancing sustainable marine tourism. The study's implications for marketing management emphasize the pivotal role of relationship marketing in cultivating positive customer emotions and its subsequent influence on sustainable marine tourism. Marketing practitioners can leverage these insights by prioritizing personalized engagement strategies and loyalty programs, strengthening emotional connections between tourists and destinations. Integrating educational initiatives, such as partnerships with environmental organizations and awareness campaigns, is essential for promoting marine conservation and sustainable practices. The study emphasizes the necessity of diverse marketing approaches to evoke positive emotional responses, offering practical guidance for marketers to benefit marine conservation efforts and enhance the tourism experience.